Pemharuh Belas Kasih Terhadap Perilaku Prososial Dimoderasi Oleh Kebutuhan Kognisi Pada Remaja Yang Kehilangan Orang Tua - Tumpuk Indrayati (Universitas Muhammadiyah Malang, 2023)
Prosocial behavior provides satisfaction and well-being for individuals. Prosocial behavior is related to great compassion. Individuals with high compassion have a sense of responsibility for the well-being of others to behave prosocially. The need for cognition moderates the influence. The aim of this study was to determine the effect of compassion on prosocial behavior moderated by cognition needs. Research subjects as many as 232 students aged 15-18 years. The research instrument used the Compassion Subscale of the Dispositional Positive Emotion Scale (DPES-CS), the Prosocialness Scale for Adults (PSA), the Need for Cognition Scale (NCS-6), Data was analyzed using Moderated Regression Analysis. The results showed that the positive influence and significantly decreased compassion towards prosocial behavior moderated by cognition needs (β = -0.072; p = 0.017). The contribution of compassion to prosocial behavior is moderated by the need for cognition, which was equal to 64.7